Improving rational number knowledge using the NanoRoboMath digital game - Kärki Tomi; McMullen Jake; Lehtinen Erno (SPRINGER, 2022)
Rational number knowledge is a crucial feature of primary school mathematics that predicts students' later mathematics achievement. Many students struggle with the transition from natural number to rational number reasoning, so novel pedagogical approaches to support the development of rational number knowledge are valuable to mathematics educators worldwide. Digital game-based learning environments may support a wide range of mathematics skills. NanoRoboMath, a digital game-based learning environment, was developed to enhance students' conceptual and adaptive rational number knowledge. In this paper, we tested the effectiveness of a preliminary version of the game with fifth and sixth grade primary school students (N = 195) using a quasi-experimental design. A small positive effect of playing the NanoRoboMath game on students' rational number conceptual knowledge was observed. Students' overall game performance was related to learning outcomes concerning their adaptive rational number knowledge and understanding of rational number representations and operations.